Dramatic Conflict: Between State and Market in the Cultural Production of Theatre in Rural China - Judd, Ellen R. (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1996)
"Dramatic Conflict" explores contemporary changes in the conditions of production of Chinese drama by focusing on the relation between state and market orientations at the core of the creative practice of state drama troupes. The article does so through utilizing the work of Bourdieu on fields of cultural production. The data are derived from fieldwork with state drama troupes on tour in the countryside in Fujian province in 1993 and 1994. Attention is given to the political economy of the organization of state drama troupes and their commercialized conditions of performance for rural communities, and also to the repertoire and ritual aspects of rural performance. The article argues that grounded state power remains central to the practice of dramatic production in China, but operates through market relations inserted into the heart of cultural production by state cultural policy.